Physical Model of the Cardiopulmonary System and its Interactions using the Object-oriented Multi-Domain Environment SIMSCAPE. - Fernández-de-Cañete-Rodríguez, Francisco Javier; Pyzh, Maryana; García-Moral, Inmaculada (My University, 2023)
Nowadays, cardiovascular diseases together with chronic obstructive pulmonary diseases represent the main causes of natural death. On a physiological level, the cardiovascular and respiratory systems are closely related as the heart and lungs are responsible for providing nutrients to the body and removing waste substances. The use of mathematical models has contributed to a greater extent to gain an insight into the internal process that take place at cardiovascular and pulmonary level. In this paper electro-hydraulic and mechanic-electrical analogies have been employed to model the cardiovascular and respiratory systems using the SIMSCAPE physical modelling environment. Results have been obtained showing an adequate performance both under physiologic and pathophysiologic situations. The objective is to provide the clinician with a benchmark to get valuable information concerning the performance of the cardiorespiratory system and its tight interrelations.
Keywords: Ingeniería biomédica; Aparato respiratorio - Modelos matemáticos; Sistema cardiovascular - Modelos matemáticos; Physical modeling; Electrical analogy; Cardiorespiratory system